Deciphering the mediating role of problem-solving skills in predicting employee turnover intention decision - Aigbogun, Osaro; Fawehinmi, Olawole; Xing, Meng; Tajuddin, Sheikh Ahmad Faiz Sheikh Ahmad (Asian Development Policy Review, 2024)
This study examines how problem-solving skills act as a mediator between external motivation, internal motivation, emotional intelligence, and employee turnover intentions. In order to achieve the objective of this study, a quantitative research approach was employed, and the survey data was collected through purposive sampling from a sample of 101 workers in China. The findings of the partial modeling analysis from Smart PLS 3 affirmed the significant influence of external motivation and problem-solving skills on employee turnover intentions. Problem-solving abilities significantly moderate the association between emotional intelligence and employee turnover intention, even though there is no substantial correlation between internal motivation and emotional intelligence in terms of employee turnover intention. However, this mediating effect is not present in the relationships between external/internal motivation and employee turnover intention. This study provides significant insights into the predictors of employees’ intention to leave the workplace in China’s Shandong Province and policy implications for retaining key employees. This study can help managers and policymakers formulate policies that increase employees’ motivation and problem-solving skills to keep them from leaving the organization. Also, this study shows that creating an organizational environment that fosters the development of emotional intelligence through coaching will help employees be resilient with problem-solving skills and remain in the organization.